TANTANGAN DAN INOVASI PELAKSANAAN MODEL MADRASAH RAMAH ANAK PADA MASA PANDEMI COVID 19 DI MI MIFTAHUL HUDA KEPANJEN MALANG - Albar, Melani; Nurhayati, Ifa; Inayati, Isna Nurul (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
Limiting social interaction during the Covid-19 pandemic is a challenge for MI Miftahul Huda in implementing the child-friendly madrasa model. The online mode of learning that is carried out, of course, must prioritize the interests and facilitate the fulfillment of children's rights. This research was conducted from April to September 2021 using a case study qualitative approach. The selection of research informants was carried out using purposive sampling technique. The data collection technique used by the researcher is using In-depth Interview, Participant Observation and document study. The results of this study indicate that: 1) The process of implementing learning at Mi Miftahul Huda during the Covid-19 pandemic was carried out by taking into account the rules and directions from the government, namely the implementation of the online learning process. 2) The innovation of implementing the Child Friendly Madrasah model is carried out by focusing learning outcomes on the cognitive and attitude aspects of students, as well as combining the implementation of limited offline mode learning in the resident prayer room with a very limited duration of learning. 3) The challenges of implementing the Child Friendly Madrasah model at Mi Miftahul Huda include the learning process, facilities and patterns of learning assistance which are still very limited. However, all of these challenges can be solved with the learning innovations that have been carried out.